Genetic contributions to the stability and satisfaction in Sexual Relationships - Kirolos Eskandar (Global Medical Genetics)
The stability and satisfaction of sexual relationships are critical determinants of individual well-being and societal cohesion. While much is known about the psychological and social factors influencing these outcomes, the genetic underpinnings remain an emerging field of inquiry. This literature review synthesizes findings from 42 peer-reviewed studies published between 2003 and 2023, exploring the genetic contributions to relationship stability and satisfaction. Key findings indicate that neuroticism, with an estimated heritability of ∼40 %, is a strong predictor of relationship instability, while agreeableness and extraversion are associated with greater relationship satisfaction. The review examines the genetic foundations of personality traits, attachment styles, emotional regulation, hormonal influences, sexual compatibility, communication styles, and mental health predispositions. Additionally, it highlights the interplay between genetic and environmental factors, presenting case studies and empirical evidence that elucidate the complex interactions at play. Ethical considerations and future research directions are discussed to provide a comprehensive understanding of how genetics can shape successful sexual relationships. By bridging the gap between genetic research and relationship science, this review offers data-driven insights to guide future investigations in this interdisciplinary domain.